Kajian Cemaran Salmonella spp pada Daging Ayam Broiler di Pasar Tradisional dan Modern Kota Bandar Lampung - Z Zairiful; Y Sukaryana; K Maghfiroh (Politeknik Negeri Lampung, 2021)
Food can be a carrier for pathogenic agents that can disease in consumers (foodborne disease). Chicken meat is one of the products from livestock which has a high consumption rate, because besides being easy to obtain, the growth of chickens is fast, and the price is also more affordable compared to large livestock types. Chicken meat is an excellent medium for microbial growth and makes it a perishable food ingredient. Foodborne illness is a disease caused by pathogenic microorganisms that contaminate food, such as Salmonella spp, Staphylococcus aureus, and Escherichia coli (E.coli). Salmonella spp infection can cause salmonellosis which irritates the digestive tract and many of them result in death. This study aims to assess the presence and number of pathogenic microorganisms Salmonella spp in broiler chicken sold in traditional and modern markets in Bandar Lampung. The research was conducted by purposive sampling of 30 chicken meat samples. Broiler chicken carcass samples were taken as whole and then stored in sterile plastic, labeled and put into a cool box filled with ice. The variables observed in this study were the presence and number of Salmonella bacteria. The data obtained were analyzed descriptively. The results of Salmonella spp examination on chicken meat samples in traditional markets in Bandar Lampung City showed a positive in 1 (one) sample or 6.7%, while in modern markets Salmonella was not found. The presence of Salmonella in chicken meat is thought to be due to contamination from the water used during the process of slaughtering and preparing the carcass, contamination from the carcass slaughtering and selling environment which does not apply good sanitary hygiene and poor personal hygiene of the traders. The conclusion obtained is that the number of Salmonella spp in chicken meat in traditional markets is not in accordance with SNI 7388 of 2009 concerning the Maximum Limit of Microbial Contamination (BMCM) in fresh meat.